Kewenangan Dinas Lingkungan Hidup Dalam Penanggulangan Polusi Akibat Pembakaran Sampah Di Kota Tangerang - Nurikah, Nurikah; Jazuli, E. Rakhmat; Bustaman, Chilla Daha Rosa (Equality : Jurnal Hukum dan Keadilan, 2024)
Tangerang City Regional Regulation Number 2 Year 2022 on Waste Management contains technical regulations on waste management and a prohibition on burning waste that is not in accordance with the technical requirements of waste management. This research focuses on: How is the Implementation of the Authority of the Tangerang City Environment Agency over waste management that affects pollution caused by waste burning based on Tangerang City Regional Regulation Number 2 Year 2022? How are the Obstacles and Solutions of the Tangerang City Environmental Agency in overcoming pollution caused by waste burning in Tangerang City? The theories used are Authority Theory and Law Enforcement Theory. The method used is the empirical juridical approach method so that the author uses a qualitative and descriptive type of research. The results obtained are that the Tangerang City Environmental Agency is responsible for managing waste by inviting the community to participate in the waste bank and waste alms program and supervising and enforcing the law on this waste burning case. There are obstacles, namely the difficulty of monitoring the waste burning area, illegal trash bins, lack of public awareness. The suggestion is to conduct an analysis in the implementation of the regulation, increase supervision at points where waste burning often occurs, eradicate illegal trash bins, improve waste management by cooperating with organizations regarding the development of waste banks, inviting the public to participate in socialization and conduct waste alms